2020
DOI: 10.26737/jetl.v5i2.2203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Screen Size on Students’ Cognitive Load in Mobile Learning

Abstract: <p>Mobile learning is becoming a crucial tool in this era of face-to-face shutdown of education, and however the whole process currently faces a significant deficiency due to the kind of cognitive load that does exist and its relation with mobile device screen display size. It is well-established that certain screen sizes are more effective than others. This study aims to investigate the effect of screen size on students’ cognitive load in mobile learning. Specifically, it investigates whether screen siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…On the other side, there were no differences in reselts between learners in urban and rural schools, but between those who used computers/notebooks and smartphones for online learning (in favour of computers/notebooks). This criterion was not examined in our research but the problem of small screen is researched, for example, by Alasmari ( 2020 ), or by Cirus et al ( 2019 ) in the Czech Republic. Specifically, the study investigates the effect of screen size on students’ cognitive load in mobile learning, and, proves that the use of an appropriately larger size improves learner’s knowledge.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…On the other side, there were no differences in reselts between learners in urban and rural schools, but between those who used computers/notebooks and smartphones for online learning (in favour of computers/notebooks). This criterion was not examined in our research but the problem of small screen is researched, for example, by Alasmari ( 2020 ), or by Cirus et al ( 2019 ) in the Czech Republic. Specifically, the study investigates the effect of screen size on students’ cognitive load in mobile learning, and, proves that the use of an appropriately larger size improves learner’s knowledge.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In addition, Park et al [33] investigated the effects of screen size (3.5" vs. 7" vs. 10.1") on the efficiency of mobile learning over time and the results indicated that screen size did not make a significant difference. On the other hand, research findings by Alasmari [34] revealed that a small screen display size produces the lowest cognitive load among university students as compared with larger displays.…”
Section: Introductionmentioning
confidence: 94%
“…Given that 68.1% of all website visits in 2020 came from mobile devices (Enge 2021), it is critical to take screen size into account when evaluating the effect of anchoring in online search. Not surprisingly, the screen size of a device has been shown to affect consumer decision making (Alasmari 2020; Kim and Sundar 2016). Research finds that smaller screen displays result in lower cognitive load than larger display screens (Alasmari 2020; Redlinger, Glas, and Rong 2021).…”
Section: Hypothesesmentioning
confidence: 99%
“…Not surprisingly, the screen size of a device has been shown to affect consumer decision making (Alasmari 2020; Kim and Sundar 2016). Research finds that smaller screen displays result in lower cognitive load than larger display screens (Alasmari 2020; Redlinger, Glas, and Rong 2021). Specifically, cognitive load, as measured by electroencephalogram studies, has been shown to increase with screen size, primarily reflecting increases in visual processing load rather than cognitive task (Redlinger, Glas, and Rong 2021).…”
Section: Hypothesesmentioning
confidence: 99%